Employee Performance: Are Influencing of Self Efficacy, Locus of Control, Goal Orientation, and Compensation? - Arifah, Nafiqotun; Darmayanti, Novi; Rosyida, Isnaini Anniswati; Zulkarnaen, Have; Handayani, Sutri; Rama, Radian Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Performance is the main basis in the activities of achieving company goals. The purpose of this study was to analyze and determine the effect of Self Efficacy, Locus of Control, Goal Orientation, and Compensation partiay or simultaneousy on Employee Performance in the Idea Business Partners Sharia Cooperative in East Java. This study uses quantitative research methods, the sample used is the entire popuation, namely 93 employees. Data analysis used uses the outer mode, inner mode and hypothesis testing using Smart-PS. The resuts of the hypothesis test of the Sef Efficacy variabe partiay have a positive and significant effect on the Kopsyah-MUI empoyee performance variabe, the Locus of Control variable partialy has a positive and significant effect on the Kopsyah-MUI employee performance variabe, the Goal Orientation variabe partialy has a positive and significant effect on the Kopsyah-MUI employee performance variable, the Compensation variable partialy has a positive and significant effect on the Kopsyah-MUI Employee Performance variable. While X1 (Self Efficacy), X2 (Locus of Control), X3 (Goal Orientation), X4 (Compensation) simultaneousy affect Y (Employee Performance).